Women Mystics, Counter-Reformation Catholicism, and Cross-Cultural Pollination. The Mystical Model in the Mediterranean and Beyond - González Fernández, Borja W. (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2024)
Despite longstanding scholarly interest, or perhaps because of it, women mystics remain trapped between the psychological interpretations of modern academia and the idealized portrayals of Church authorities, making them figures that are still largely unknown and misunderstood. Moving beyond the limitations of psychological and theological interpretations that reduced these women’s experiences, this article will compare and contrast the lives of several mystics living at the turn of the modern era. It will argue that their ability to challenge societal norms and create spaces for female community relied on their meticulous adherence to a specific behavioral pattern known as the ‘mystical model,’ consisting of conversion, foundation, and teaching. The careful execution of these steps across diverse cultures and geographies not only validated their deeply personal religious experiences but also granted social legitimacy to the public expressions of their spirituality. Born and developed around the wider Mediterranean, as classically defined by Braudel, the mystical model came to transcend the borders of the Mare Nostrum with the missionary effort that accompanied the colonial expansion characteristic of the European Age of Discovery. Aided by the printing press and in the context of the assertive and militant Catholicism emerging in the wake of the Council of Trent, missionaries, in their quest to physically expand the horizons of the Roman Church, were instrumental in diffusing the privatized, individualist religious spirit irradiating from early modern Europe. Consequently, female religious vocations started to emerge in societies where women’s role in religion – and in public life – had been largely marginal. This phenomenon also contributed to the formation of new frames of reference, new archetypal categories, awarding these women with social sanction for their recently acquired religious self-awareness, as this article will prove. Examining the extra-Mediterranean expansion of the mystical model will underscore that the missionary effort cannot be exclusively understood in a one-directional sense. Instead, it must be seen as a pluri-directional phenomenon, a process of cross-cultural pollination that transformed both catechist and catechumen, simultaneously broadening their respective systems of collective representations.